Epidemiological study of animal bite victims: A study from a tertiary care hospital of Central India - Arindam Maiti,; Sharma, Arvind; Sunita Patel,; Ashish Mishra, (Asian Journal of Medical Sciences, 2025)
Background: Rabies is a dreadful viral zoonotic disease with potential threat caused by bite of animals such as dogs, cats, monkeys, and wild animals such as foxes and jackals with number increased from 42 lakhs in 2012 to 72 lakhs in 2020 as per integrated disease surveillance project. Aims and Objectives: The aim of the study was to identify the epidemiology and to find the association with the various factors among animal bite victims. Materials and Methods: This study was a cross-sectional study conducted among animal bite victims for a period of 1 year, till the completion of a desired sample size of 542 in a tertiary care hospital, Jabalpur. Data collection was done by means of pre-tested, self-structured questionnaire with face-to-face interview technique after taking written informed consent among them. Data entered in MS-Excel, descriptive and inferential statistical analysis was done using IBM-SPSS v27.0 software. Results: In this study, the mean age among the victims was observed to be 30.58±17.30 years with the majority belonged to 21–30 years, that is, 22.32%. Maximum were bitten by dogs 86.72% with unprovoked type of bite 77.68% and Category-III type of wound 63.84% at lower limb 65.68% during monsoons 255 (47.05%). Those reported with unprovoked bite majority were adults 352 (83.61%); odds ratio=0.10(0.06–0.16); P=0.001. Conclusions: Majority victims were adult males and were bitten by stray dogs with unprovoked type of bite during monsoon season. Those reported with unprovoked type of bite majority were adults, while provoked type among children and lower education level ones due to the difference in education, behavior pattern, and attitude toward animals.